Metaphors We Die By? Geoengineering, Metaphors, and the Argument From Catastrophe. - Nerlich, Brigitte; Jaspal, Rusi (Metaphor & Symbol, 2012)
Geoengineering the climate by reflecting sunlight or extracting carbon dioxide from the atmosphere has attracted increasing attention from natural scientists, social scientists, policy makers and the media. This article examines promotional discourse related to geoengineering from the 1980s to 2010. It asks in particular how this option for dealing with the problems posed by climate change were framed through the use of conceptual and discourse metaphors and whether one can argue that these are metaphors we “live by” or metaphors we might “die by.” Findings show that an overarching argument from catastrophe was bolstered by three conceptual master-metaphors, namely “THE PLANET IS A BODY,” “THE PLANET IS A MACHINE,” and “THE PLANET IS A PATIENT/ADDICT,” linked to a variety of discourse metaphors, older conceptual metaphors, and clichés. This metaphorical landscape began to shift while the article was being written and will have to be closely monitored in the future.